Spectral-Difference Method for Two-Dimensional Compressible Fluid Flow (Journal of Computational Mathematics, 1998)
We develop a combined Fourier spectral-finite difference method for solving 2-dimensional, semi-periodic compressible fluid flow problem. The error estimation, as well as the convergence rate, is presented.